Une « boîte noire » à manipuler soigneusement : L’analyse des coûts et des bénéfices sociaux de l’entreprise multinationale - Bonin, Bernard (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1985)
This paper assumes that the analysis of the social costs and benefits of the MNE is not only possible but also necessary. This kind of analysis is not easy because there are different rival theoretical models, because of the oligopoliste market structures that characterize multinational industries, and because the often clashing interest of home and host countries. However the author is able to identify the main costs and benefits for each group of countries. The home countries are often able to export products and factors, and to import steady flows of cheap raw materials and intermediate goods thanks to MNE. However they risk the loss of taxes, jobs and capital; besides they can suffer from MNE speculation against their own currency and balance of payments imbalances. Host countries show positive gains in terms of economic development, and eventual access to foreign markets. However they can loose taxes, suffer the extra-territorial implementation of home countries' laws and policies as well as transfer-pricing and balance-of-payments desequilibra.